Karakteristik Organoleptik Selai Kacang Merah (Phaseolus vulgaris L) dengan Variasi Penambahan Gula Pasir - Derlean, Supriyadi; Breemer, Rachel; Mailoa, Meitycorfrida (Universitas Pattimura, 2024)
Indonesia has many types of nuts with various colors, varieties, and shapes, which have great potential to add variety and nutrition to different patisserie products. One of them is red beans (Phaseolus Vulgaris L), which is a type of legume that has the highest carbohydrate content, protein content equivalent to green beans, much lower fat content than soybeans and peanuts and is also often used as an ingredient in making jam. This research aims to determine the appropriate sugar concentration on the organoleptic characteristics of red bean butter. The research was designed using a single factor. A completely randomized design with additional sugar concentration treatment consisting of 3 treatment levels of 30, 40, and 50%. The research results show that the addition of 50% sugar concentration is the best concentration based on the results of organoleptic tests, which include hedonic tests, like color (2.64), like taste (3.04), like texture (3.24), like aroma (3.24), Overall like is close to very like (3.64). Hedonic quality test for chocolate color (3.08), red bean aroma (3.36), soft texture (3.28), and red bean taste (3.24).